(3GdQaOI aj eYfi hMOIs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3hHYO, agPg YLGdI eSeGI HGdQaOI aj eYfi hMOg, cGf GdOGYj EdjgG Cf GdReNTQj bGd aj bhdg JYGdi(B: "(3hYdjgG hYdi Gdadc JMedhf(B" s
(3BNQgG (B:s
(3dCf ebUhO GdTGYQ Cfg de jUfY TjFkG efg adPdc QaY hdhdG Pdc fUH cdg Je GdQSGdI HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3hHBNQgG UhQI bQGAI fajSI hLOJ aj CUd GdeDda cJHgG HNWg hEPf efg HQhGjJgG efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B106 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B102 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B147 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs